The Sinai Robotic Surgery Trial in HPV-related oropharyngeal squamous cell carcinoma (SIRS 2.0 trial) – study protocol for a phase II non-randomized non-inferiority trial - Chai, Raymond L.; Ferrandino, Rocco M.; Barron, Christine; Donboli, Kianoush; Roof, Scott A.; Khan, Mohemmed N.; Teng, Marita S.; Posner, Marshall R.; Bakst, Richard L.; Genden, Eric M. (Frontiers in Oncology, 2022)
Background Human papillomavirus associated oropharyngeal squamous cell carcinoma (HPVOPSCC) usually affects a younger patient population. As such, the risk for long term toxicity associated with therapy is an important consideration. Multiple trials focused on de-escalation of therapy to preserve survival outcomes while minimizing treatment toxicity are currently in progress, however the question of which patients are ideal candidates for de-escalation remains unanswered. Circulating tumor DNA (cfHPVDNA) has emerged as a means of monitoring disease in patients with HPVOPSCC. Undetectable postoperative cfHPVDNA levels portend a better prognosis and by extension, may identify ideal candidates for de-escalation therapy. We propose an overview and rationale for a new institutional clinical trial protocol focusing on the use of cfHPVDNA to risk stratify patients for adjuvant therapy. We hypothesize that many surgical patients currently receiving radiation therapy may be clinically observed without adjuvant therapy. Methods Patients with measurable cfHPVDNA and clinically resectable HPVOPSCC will undergo TORS resection of tumors and neck dissection. Patients with undetectable cfHPVDNA at 3 weeks post-op will be allocated to low or high-risk treatment protocol groups. The low risk group consists of patients with <4 positive lymph nodes, ≤2 mm extranodal extension (ENE), and perineural invasion (PNI) or lymphovascular invasion (LVI) alone. The high-risk group is made up of patients with ≥4 positive lymph nodes, gross ENE, positive margins, N2c disease and/or the combination of both PNI and LVI. The low-risk group will be allocated to an observation arm, while the high-risk group will receive 46 Gy of adjuvant radiotherapy and weekly cisplatin therapy. The primary outcome of interest is 2-year disease recurrence with secondary outcomes of 2-year disease free survival, locoregional control, overall survival, and quality of life measures. A sample of 126 patients in the low-risk group and 73 patients in the high-risk group will be required to evaluate non-inferiority to the standard of care. Discussion This study will provide much needed recurrence and survival data for patients that undergo primary TORS followed by observation or de-escalated adjuvant therapy. Additionally, it will help delineate the role of cfHPVDNA in the risk stratification of patients that undergo treatment de-intensification.